Effect of Heat Treatment on Wear Performance of Nanostructured WC-Ni/Cr HVOF Sprayed Coatings - Tarek Ben Mahmud (Japanese Society of Tribologists, 2017)
The extraction and processing of bitumen from oil sands exposes machinery parts to constant abrasive wear which can cause severe surface degradation and component failure, resulting in production shut-downs. To reduce the effect of wear on performance of production machinery, wear resistant coatings must be used to extend component life. Recently, thick microstructured cermet coatings based on WC dispersions have been used to protect surfaces. In this study a nanostructured 83WC-17Ni/Cr coating was deposited on to C-Mn steel surfaces using High Velocity Oxy-Fuel (HVOF) spraying. The effect of heat treatment in air and nitrogen atmosphere on changes in the microstructure, hardness and wear resistance was investigated. The results showed that both the hardness and wear resistance increased with increasing heat treatment temperature in both air and nitrogen atmosphere. However, the use of heat treatments in air led to the formation of brittle metal oxides which resulted in micro-cracking within the coatings. This caused the coatings to fail by brittle fracture during wear testing. In comparison heat treatment in nitrogen produced better wear resistance because metal oxide formation was avoided.